The History of Orientalist Quran Translation - Luthfia Shifaul Amanah Burhani; Annisa Fitri (Institut Agama Islam Sumatera Barat, 2023)
The orientalists' belief in the Qur'ān as a product of human intervention is one of the reasons why Western scholars of Islam study the Qur'ān. Then the crusades that took place between 1095 and 1291, also caused political and religious friction between Western Christians in Palestine and Islam, which had an impact on the spirit of Christian apologetics and their interest in translating the Qur'an in order to try to overthrow Islam with refutation and hatred of the Qur'an. The author focuses on analyzing the history of the emergence of orientalism to the process of translating the Qur'an which includes the periodisation of translation to the development of Qur'anic translation methods from time to time. This research is a type of qualitative research with a library research model using data sources in the form of books, encyclopaedias, dictionaries, and the like. The results of this research show that the study of Islam by orientalists in making translations of the Qur'an began with a Christianisation mission with the aim of insulting the Qur'an. But along with the times, the translation of the Qur'an changed its approach to become more scientific, critical and objective. So that some of the results of their research also contribute to Islam.